HCC recurrence in HCV‐infected patients after liver transplantation: SiLVER Study reveals benefits of sirolimus in combination with CNIs – a post‐hoc analysis. (15th May 2020) - Werner, Jens M.; Hornung, Matthias; Krah, Rubertha; Götz, Markus; Schnitzbauer, Andreas A.; Schlitt, Hans J.; Geissler, Edward K.; ,
Summary: Factors affecting outcomes in liver transplant (LTx) recipients with hepatocellular carcinoma (HCC) and hepatitis C viral (HCV) infection include the choice of immunosuppression. Here, we analyzed the HCV + subgroup of patients from the randomized controlled, international SiLVER Study. We performed a post hoc analysis of 166 HCV + SiLVER Study patients regarding HCC outcome after LTx. Control patients (group A: n = 88) received mTOR inhibitor (mTORi)‐free, calcineurin inhibitor (CNI)‐based versus sirolimus‐based immunosuppression (group B: n = 78). We found no significant difference regarding HCV‐RNA titers between group A and B. Since no effect in group B could be due to variable sirolimus dosing, we split group B into patients receiving sirolimus‐based immunosuppression + CNIs for >50% (B1; n = 44) or <50% (B2; n = 34) of the time. While there remained no difference in HCV‐RNA titer between groups, HCC recurrence‐free survival in group B1 (81.8%) was markedly better versus both group A (62.7%; P = 0.0136) and group B2 (64.7%; P = 0.0326); Interestingly, further subgroup analysis revealed an increase ( P = 0.0012) in liver enzyme values in group B2. Taken together, in HCV‐infected patients with HCC and LTx, mTORi immunosuppression + CNIs yields excellent outcomes. Unexpectedly, higher levels of liver inflammation and poorer outcomes occur with mTORi monotherapy in the HCV + subgroup.